Readiness Analysis of the ISO 9001:2015 Certification in The Magister Program of Industrial Engineering UPN “Veteran” Yogyakarta Using Gap Analysis - Sadi; Agus Ristono; Hidayat Saputra (Technium Social Sciences Journal, 2020)
The competition within the field of education, especially the postgraduate program, and the market demand oblige master study programs to build and develop an internal management system, based on the standards determined by the government. Due to the increasingly strict competition for the postgraduate education, many master study programs have adopted and implemented the quality improvement program effectively. Such quality improvement program is in the Quality Management System (QMS). The development of this system is the ISO 9001 standard certification. The ISO 9001 certification is a standard that contains the requirements of the quality management system initiated by the International Organization for Standardization (IOS). The institution that this research studied was the industrial engineering master program (MTI) at UPN "Veteran" Yogyakarta. This study program had several data weaknesses in its student management system, academic system, payment system, and others. Such problems were the indirect impacts due to the absence of the ISO 9001 certification at MTI of UPN “Veteran” Yogyakarta. This research aimed to evaluate the current condition at MTI of UPN "Veteran" Yogyakarta, and how it readiness was for the preparation of the ISO 9001:2015 certification, and also provided recommendations as well as compiled the study program quality documents that were in line with the ISO 9001:2015 requirements. This research used the Gap Analysis Method. The Gap Analysis was applied to evaluate the existing conditions at MTI of UPN “Veteran” Yogyakarta, and then assessed the readiness of MTI of UPN “Veteran” Yogyakarta for the implementation of the ISO 9001:2015 certification. The Gap Analysis calculation used the checklist that was made based on the ISO 9001:2015 requirements. The calculation results using the checklist would show how much the readiness of the MTI of UPN “Veteran” Yogyakarta was to conduct the ISO 9001:2015 certification.